Tablets, touchscreens, and touchpads: How varying touch interfaces trigger psychological ownership and endowment - Brasel, S. Adam; Gips, James (Journal of Consumer Psychology, 2014)
AbstractAs mouse‐driven desktop computers give way to touchpad laptops and touchscreen tablets, the role of touch in online consumer behavior has become increasingly important. This work presents initial explorations into the effects of varying touch‐based interfaces on consumers, and argues that research into the interfaces used to access content can be as important as research into the content itself. Two laboratory studies using a variety of touch technologies explore how touchscreen interfaces can increase perceived psychological ownership, and this in turn magnifies the endowment effect. Touch interfaces also interact with importance of product haptics and actual interface ownership in their effects on perceived product ownership, with stronger effects for products high in haptic importance and interfaces that are owned. Results highlight that perceptions of online products and marketing activities are filtered through the lens of the interfaces used to explore them, and touch‐based devices like tablets can lead to higher product valuations when compared to traditional computers.